Are Veterinary Students Using Technologies and Online Learning Resources for Didactic Training? A Mini-Meta Analysis - Edlira Muca; Damiano Cavallini; Rosangela Odore; Mario Baratta; Domenico Bergero; Emanuela Valle (MDPI AG, 2022)
Over the last years, there has been an increase in online educational resources and media device use for educational purposes in veterinary settings. However, an overall analysis of these studies providing measurements of the use of learning resources and media devices could be particularly useful for veterinary teachers. The evolution of technology, coupled with the advent of pandemic-related restrictions in person lessons, has made it imperative that educators consider how students may access educational material, as well as what type of educational material may be available to them. Databases including PubMed, Scopus, CAB Abstracts, and Web of Sciences were searched for relevant studies from January 2012 to June 2022. A mini-meta-analysis for proportions was performed using RStudio. Results highlight a high use of portable media devices with differences among countries, continued good use of traditional textbooks, moderate use of online tools, and low use of research papers. The results suggest that despite living in a technologically advanced world, veterinary students have attitudes towards digital resources that cannot be assumed.